A Single Bout of Exercise Provides a Persistent Benefit to Cognitive Flexibility. Issue 3 (3rd July 2022) - Shukla, Diksha; Heath, Matthew
ABSTRACT: Purpose: A single bout of exercise enhances activity within the cortical networks that support executive function. It is, however, unclear whether exercise improves each core component of executive function and for how long a putative benefit might persist. Method: In Experiment 1, participants completed 20-min of aerobic exercise (via cycle ergometer) and cognitive flexibility—a core component of executive function—was examined pre-exercise, and at immediate, 30- and 60-min post-exercise assessments. Experiment 2 entailed a non-exercise control (i.e., participants sat on the ergometer without exercising) involving the same timeline of cognitive flexibility assessment. Cognitive flexibility was measured via stimulus-driven (SD) and minimally delayed (MD) saccades arranged in an AABB paradigm. SD and MD saccades require a response at target onset and after target offset, respectively, with the latter requiring executive control. Work has shown that reaction times for a SD saccade preceded by a MD saccade are longer than when a SD saccade is preceded by its same task-type, whereas the converse switch does not influence performance (i.e., the unidirectional switch-cost ). Results: Experiment 1 showed a unidirectional switch-cost at each assessment; however, the switch-cost magnitude was decreased at immediate and 30-min assessments compared to the pre- and 60-min assessments. In contrast, Experiment 2 did not elicit a change in switch-cost magnitude across the different assessments. Discussion/Conclusion: Thus, a single-bout of exercise benefitted the cognitive flexibility component of executive function in the immediate and 30-min post-exercise assessments.